GAMBARAN HUNIAN WARGA YANG TINGGAL DI AREA TPA NGRONGGO-SALATIGA TERHADAP PREVALENSI TUBERKULOSIS PARU - Puspita, Dhanang; Fitrianto, Agus; ., Dary; Wijaya, Yunita Christina (Universitas Kristen Satya Wacana, 2018)
Population growth rate faster than the availability of resindential land will affect the decrease in health status. Population with low socioeconomic who work as scavengers will be very difficult to live in proper residential areas. Those people choose to live around the location of Landfills. This option becomes a consideration because the price is relatively cheap and close to the work location. A landfills environment condition isn’t proper for health and it makes the people who lived there suspectible of health problems. One of the most common diseases is Pulmonary Tuberculosis. This disease occurs due to bacterial infection and supported by unhealthy environment. The area around Ngronggo Landfills in Salatiga becomes one of places to stay for scavengers. The purpose of this research is to describe the influence of the house physical environment toward incident of pulmonary tuberculosis to the people who living in Landfills area. This research used descriptive quantitative method. Technique collecting data are observation, interview and environmental condition measurement with temperature parameter, humidity and light intensity. The condition of non-qualified houses is 73% of lighting, 98% of humidity, 80% of ventilation, 91% of flooring and 98% of garbage smell. The conclusion is most houses of residents living around the Landfills in Ngronggo Salatiga isn’t eligible for health requirements and become contributors’ infection of pulmonary tuberculosis.